2018
DOI: 10.3390/nu10091171
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β2, EGF, and FGF21 Growth Factors Present in Breast Milk Promote Mesenteric Lymph Node Lymphocytes Maturation in Suckling Rats

Abstract: Breast milk, due to its large number of nutrients and bioactive factors, contributes to optimal development and immune maturation in early life. In this study, we aimed to assess the influence of some growth factors present in breast milk, such as transforming growth factor-β2 (TGF-β2), epidermal growth factor (EGF), and fibroblast growth factor 21 (FGF21), on the immune response development. Newborn Wistar rats were supplemented daily with TGF-β2, EGF, or FGF21, throughout the suckling period. At day 14 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 41 publications
0
20
1
Order By: Relevance
“…Some authors researched the effects of TGF-β2, EGF and FGF21 -growth factors present in breast milk- on GALT, but scarce evidence exists regarding the effects of these bioactive factors on systemic immunity in newborn rats [ 37 ]. Previously, some research performed by our group demonstrated the effect of the supplementation with TGF-β2, EGF and FGF21 on the promotion of intestinal lymphocyte maturation in newborn suckling rats [ 25 ]. The present study was designed to determine whether daily supplementation with these three GF could promote systemic immune development during the postnatal period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some authors researched the effects of TGF-β2, EGF and FGF21 -growth factors present in breast milk- on GALT, but scarce evidence exists regarding the effects of these bioactive factors on systemic immunity in newborn rats [ 37 ]. Previously, some research performed by our group demonstrated the effect of the supplementation with TGF-β2, EGF and FGF21 on the promotion of intestinal lymphocyte maturation in newborn suckling rats [ 25 ]. The present study was designed to determine whether daily supplementation with these three GF could promote systemic immune development during the postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were incubated for 48 h at 37 °C and 5% CO 2 . Four hours before the end time of the incubation, 5-bromo-2’-deoxyuridine (BrdU, 20 μL/well, Merck) was added in order to measure its incorporation as an indicator of DNA synthesis in a colorimetric immunoassay [ 25 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were isolated from the MLNs of dams by passing the tissue through a 40 µm mesh cell strainer (Thermo Fisher Scientific, Barcelona, Spain). Then, the cell suspension was centrifuged (538× g, 10 min, 4 • C) and resuspended in Roswell Park Memorial Institute (RPMI) 1640 medium (Sigma-Aldrich, Madrid, Spain) enriched with 10% fetal bovine serum (FBS; Sigma-Aldrich), 100 IU/mL streptomycin-penicillin (Sigma-Aldrich), 2 mM L-glutamine (Sigma-Aldrich) and 0•05 mM 2-β-mercaptoethanol (Merck Millipore), as in previous studies [56]. CountessTM Automated Cell Counter (InvitrogenTM, Thermo Fisher Scientific) was used for cell counting and the assessment of viability.…”
Section: Lymphocyte Isolation From Mesenteric Lymph Nodes (Mlns)mentioning
confidence: 99%